Malaysia’s foreign policy under the Pakatan Harapan government: the first hundred days - Hossain, Ishtiaq (Center of Research and Intercommunication Knowledge, 2018)
The much anticipated 14th General Elections (GE-14) in Malaysia was held on May 9, 2018. A coalition of opposition political parties known as Pakatan Harapan (PH) – Alliance of Hope – confounding election-watchers at home and abroad, swept to power at the federal and nine State governments, defeating Barisan Nasional (National Front) or BN as commonly known. This policy paper aims to present a framework of foreign policy of the new PH government in Malaysia during the first 100 days. However, caution should be made that this government has been in power only since May 10, 2018. In other words, it is too early to make any final assessment of the new government’s foreign policy. However, we could try to present a contour of the new government’s foreign policy by examining the Election Manifesto of PH and by analysing statements made so far by key figures of the PH government on the country’s relations with other countries. So, at first, this report examines the Election Manifesto of PH,and explains the relevant promises made relating to the country’s foreign policy. Secondly, the policy paper would discuss Malaysia’s relations with China. Third, Malaysia’s relations with Singapore will be looked at. Third, a discussion would also focus on the Middle East countries with special focus on Saudi Arabia. Finally, a number of policy recommendations would be made for Saudi Arabia to follow towards Malaysia.